Loss of fragile WWOX gene leads to senescence escape and genome instability - Cheng, Hui-Ching; Huang, Po-Hsien; Lai, Feng-Jie; Jan, Ming-Shiou; Chen, Yi-Lin; Chen, Szu-Ying; Chen, Wan-Li; Hsu, Chao-Kai; Huang, Wenya; Hsu, Li-Jin (Cellular and molecular life sciences : CMLS, 2023)
Induction of DNA damage response (DDR) to ensure accurate duplication of genetic information is crucial for maintaining genome integrity during DNA replication. Cellular senescence is a DDR mechanism that prevents the proliferation of cells with damaged DNA to avoid mitotic anomalies and inheritance of the damage over cell generations. Human WWOX gene resides within a common fragile site FRA16D that is preferentially prone to form breaks on metaphase chromosome upon replication stress. We report here that primary Wwox knockout ( Wwox −/− ) mouse embryonic fibroblasts (MEFs) and WWOX-knockdown human dermal fibroblasts failed to undergo replication-induced cellular senescence after multiple passages in vitro. Strikingly, by greater than 20 passages, accelerated cell cycle progression and increased apoptosis occurred in these late-passage Wwox −/− MEFs. These cells exhibited γH2AX upregulation and microsatellite instability, indicating massive accumulation of nuclear DNA lesions. Ultraviolet radiation-induced premature senescence was also blocked by WWOX knockdown in human HEK293T cells. Mechanistically, overproduction of cytosolic reactive oxygen species caused p16 Ink4a promoter hypermethylation, aberrant p53/p21 Cip1/Waf1 signaling axis and accelerated p27 Kip1 protein degradation, thereby leading to the failure of senescence induction in Wwox -deficient cells after serial passage in culture. We determined that significantly reduced protein stability or loss-of-function A135P/V213G mutations in the DNA-binding domain of p53 caused defective induction of p21 Cip1/Waf1 in late-passage Wwox −/− MEFs. Treatment of N -acetyl- l -cysteine prevented downregulation of cyclin-dependent kinase inhibitors and induced senescence in Wwox −/− MEFs. Our findings support an important role for fragile WWOX gene in inducing cellular senescence for maintaining genome integrity during DDR through alleviating oxidative stress.